Odpowiedzi

2010-04-14T16:12:45+02:00
1.y=2x-4
8-4x=2 /-8
y=2x-4
-4x=-6 /:(-4)
y=2x-4
x=6/4=3/2=1,5
y=2 razy 1,5-4
x=1,5
y=3-4
x=1,5
y=1

2.6x-5=4y
2-4x=-2y /:(-2)
6x-5=4y
-1+2x=y
6x-5=4(-1+2x)
-1+2x=y
6x-5=-4+8x /-6x
-1+2x=y
-5=-4+2x /+4
-1+2x=y
-1=2x /:2
-1+2x=y
-1/2=x
-1+2 razy (-1/2)=y
-1/2=x
-2=y
-1/2=x

3. x-5y-5=0 /-x
3x+y-1=0
-5y-5=-x /:-
3x+y-1=0
5y+5=x
3(5y+5)+y-1=0
5y+5=x
15y+15+y-1=0
5y+5=x
16y+14=0 /-14
5y+5=x
16y=-14 /:16
5y+5=x
y=-14/16=-7/8
5 razy (-7/8)+5=x
y=-7/8
-4 i 3/8+5=x
y=-7/8
x=5/8